Landlocked Countries, Institutions and Economic Dynamics - Rivero, Roger Alejandro Banegas; Ramirez, Marco Alberto Nunez; Mendivil, Yesenia Clark (Asian Economic and Financial Review, 2020)
This study moves away from the use of conventional methods such as standard regressions to evaluate the hypothesis of a negative effect of a landlocked country on economic growth and other variables. An alternative approach was used based on a dynamic stochastic general equilibrium model (DSGE). The main estimation reflected a permanent shock of -2% on Non-Maritime Gross Domestic Product. To this end, the model was calibrated with parameters of the Bolivian economy (landlocked country) and the presence of similar behavioral economies with sea presence in observational equivalence (comparative countries) for impact evaluation purposes. Likewise, the role of institutional quality represented approximately 20% in the variability of the country's aggregate production (GDP), with the inference that institutional innovations could reduce and mitigate by 68% the negative effect of being a landlocked condition (mitigating action and structural challenge).